IgT Plays a Predominant Role in the Antibacterial Immunity of Rainbow Trout Olfactory Organs - Dong, Fen; Yin, Guang-mei; Meng, Kai-feng; Xu, Hao-yue; Liu, Xia; Wang, Qing-chao; Xu, Zhen (Frontiers in Immunology, 2020)
The olfactory organs (OOs) of vertebrates play important roles in their extraordinary chemosensory capacity, a process during which they are continuously exposed to environmental pathogens. Nasopharynx-associated lymphoid tissue (NALT) contains B cells and immunoglobulins (Igs), which function as the first defense line against antigens in mammals and also exist in teleosts. However, the immune responses of teleost NALT B cells and Igs during bacterial infection remain largely uncharacterized. In this study, rainbow trout were infected with Flavobacterium columnare via continuous immersion, after which the adaptive immune responses within NALT were evaluated. F. columnare could invade trout nasal mucosa and cause histopathological changes in trout OO. Moreover, the accumulation of IgT+ B cells in trout nasal mucosa was induced by bacterial challenge, which was accompanied by strong bacteria-specific IgT responses in the nasal mucus. Importantly, our study is the first to report local nasal-specific immune responses in teleosts during bacterial challenge by characterizing the local proliferation of IgT+ B cells and generation of bacteria-specific IgT in trout OOs after F. columnare infection. In addition to the strong IgT and IgT+ B cells responses in OO, bacteria-specific IgT and IgM were also detected in serum following bacterial challenge. Taken together, our findings suggest that IgT functions as an important mucosal Ig in teleost NALT and mediates local adaptive immunity during bacterial infection, which is similar to their protective role during parasitic infection.